Modifying Sensory Afferences on Tablet Changes Originality in Drawings - Bitu, Fabien; Galinon-Mélénec, Béatrice; Molina, Michèle (Frontiers in Psychology, 2022)
According to some recent empirical studies revealing that creativity is linked to sensorimotor components, the current research was aimed at evaluating whether sensory afferences could modulate originality in drawing of children and adolescents. Sixty-nine children from 1st, 3rd, 6th, and 8th grades were required to produce a man who exists and a man who doesn’t exist with finger or stylus on tablet and with pen on paper. Drawings were assessed with an originality scale comparing original drawings to unoriginal ones. Since, in comparison to drawings made on paper with a pen, drawing with finger enhances proprioceptive information, this condition was expected, according to cognitive load theory, to favor originality in drawing by reducing cognitive resources devoted to motor control of the graphic gesture (lowering intrinsic load). On the contrary, since the use of a stylus involves a proprioceptive loss of information, which enhances intrinsic load by increasing cognitive resources devoted to motor control, it was expected that drawing with stylus on tablet would lead to the least original drawings. Results only partially confirmed these hypotheses. While the use of finger on tablet led to the highest original scores, using a stylus on tablet did not impair originality in drawing of children and adolescents. In the opposite, the use of a stylus led 3rd to 8th graders to perform better than with pen on paper. This modulation of the tool on originality does not confirm the hypotheses formulated in accordance with the cognitive load framework. However, it could be explained according to an embodied perspective of creativity considering creative process as relying on a sensorimotor prediction process in which sensory afferences are central to generate and evaluate creative ideas. This research opens new avenues on creativity and proposes to consider the development of predictive motor control as a significant part of creativity development.